Evaluating The Utilization Of Physics Laboratories in High Schools: A Case Study at SMAN 5 Metro - Riswanto, Riswanto; Suseno, Nyoto; Prastiti, Wari; Octavia Rosa, Friska; Utama Hartanto Setya Putra, Dian; Afifah, Febi; Saputri, Anggun Saputri (Department of Physics Education, Universitas Mataram, 2025)
This study aims to evaluate the utilization of the physics laboratory at SMA Negeri 5 Metro and to identify factors influencing its effectiveness in supporting physics learning. A qualitative descriptive method was employed, involving Grade XI students and physics teachers as research participants. Data were collected through observations, interviews, and a response questionnaire. Analysis was conducted both during and after data collection using triangulation by comparing data from these three sources. The findings reveal that 80% of students reported suboptimal use of the laboratory, and 86.4% expressed a lack of interest in physics, primarily due to difficulties in understanding the subject matter. Physics practicals are still carried out in classrooms, with teachers bringing equipment to demonstrate experiments. Several factors hinder optimal laboratory use, including the absence of laboratory assistants or technicians, poor laboratory management, and the use of laboratory space for non-academic activities such as MGMP meetings and student council events. This study is limited to a single school (SMA Negeri 5 Metro) and does not compare laboratory use with that of other institutions, which may limit the generalizability of the findings. Future research should involve comparative studies across multiple schools to obtain a broader understanding of laboratory management and its impact on physics learning outcomes.